Weryfikacja efektów termomodernizacji budynku użyteczności publicznej = The effects of public building thermomodernization processes - Nadolna, Marzena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The process of thermomodernization is preceded by the development of an energy audit indicating the most optimal solution, which will be achieved by certain amount of energy and environmental effects. Based on the specific effects the investor can apply for funding of structural investment funds from EU. After completion of the work associated with the thermal efficiency of the building were analyzed and compared the effects with guidelines.
Keywords: termomodernizacja; audyt energetyczny; emisja zanieczyszczeń; thermomodernization; energy audit; emissions